Strategy to Improve the Performance of The Ngagel I Water Treatment Plant (IPA) in Pdam Surya Sembada Surabaya City Through Increasing Pump Efficiency - Rezhi Dika Indra; Ade Syaiful Rachman; Wafiyuddin Wafiyuddin; Eddy Setiadi Soedjono (Jurnal Indonesia Sosial Teknologi, 2024)
PDAM Surya Sembada Surabaya’s energy cost in 2021 amounted to Rp 147.654.439.569, with an energy cost ratio of 24.37%, and the electricity cost of production unit accounted for 76% of the total energy consumption of PDAM. The relatively flat topography does not allow gravity-based systems for water supply. Aging equipment has decreased overall pump efficiency (ηpt) and increased energy consumption, particularly in Ngagel I WTP, built in 1922, necessitating an energy audit. Energy audit includes measuring pump flow rate and pressure, power, voltage, current, power factor, pump and motor pump rotation and temperature. Analysis shows that raw water pumps U2, U3, U5, and S1 and distribution pumps U1, U3, and T4 are still in good condition. However, raw water pump U6 and distribution pumps U6, S1, and S2 require reconditioning and impeller adjustment due to declining efficiency. Furthermore, PDAM must inspect the distribution pump T1 with the lowest efficiency value (49.77%) to determine the appropriate repairs. The research results are action recommendations expected to serve as input and considerations for PDAM in their efforts to improve energy efficiency.